Evaluation of recycled crushed concrete as aggregate substitute in asphalt mixtures - Eldeen, Gailan Ismat Safa (2018)
The amount of crushed cement concrete continues to increase daily as a result of the demolition of old structures, thereby increasing pollution. To cope with the pressure imposed by the rise in environmental awareness and the stringent disposal regulations set by environmental protection agencies, effective measures for handling and disposing of crushed concrete must be implemented. Instead of simply disposing of crushed concrete, alternative efforts should be considered to utilize it as a recyclable material. The objective of this study was to evaluate the use of recycled concrete aggregate (RCA) as an aggregate substitute in asphalt mixture for pavement construction. However, owing to the poor physical properties of crushed concrete in terms of absorption, abrasion and specific gravity, this study focused on recycled concrete aggregate (RCA) with a passing and retained sieve size of 5 mm and 1.18 mm, respectively. In order to take into considerate abrasion and absorption properties. The physical and chemical properties were evaluated for both RCA and natural aggregate, and the recommendation is to mix crushed concrete with conventional aggregates from natural sources. Then, suitable mixtures of crushed concrete and conventional aggregates were determined based on the combinations of five types of gradation (upper, lower, medium and two others) with six different proportions of recycled concrete aggregate (0%, 20%, 40%, 60%, 80% and 100%). The degradation that occurred in the aggregate after compaction was determined, and the feasibility of using RCA in asphalt mixtures was evaluated. Aggregate degradation analysis was performed using a newly developed testing method. Then, volumetric properties and Marshall Stability were determined for all the groups. Rutting performance was evaluated for all the mixtures via repeated load axial test at different temperatures. Three factors, namely, total permanent strain, intercept and slope, and creep rate, were used to evaluate the performance of the mixtures. Moisture damage resistance was assessed for all the mixtures using a modified Lottman test. In this study, it was found that coarse RCA has a higher abrasion value a, whereas fine RCA has a higher absorption value. Absorption value increased with decreasing aggregate size. Therefore, balance should be achieved between absorption and abrasion values. In addition, RCA passed through a sieve size of 1.18 contained more cement than other fractions. Aggregate gradation exerted greater effects on aggregate degradation, Marshall Stability, and resilient modulus (MR) than RCA proportion. RCA content had a negative effect on the rutting life of hot mix asphalt (HMA) mixtures and moisture damage. The most important finding of this study is that median gradation is the best and most economical gradation for hot mix asphalt HMA that contained RCA. RCA can be used successfully up to 80%, 60%, and 40% for median, upper, and lower gradations, respectively. Moreover, the Resilient Modulus considerably affects moisture damage and rutting performance. Lastly, RCA can be used successfully in mixtures and satisfy requirements when the appropriate fraction of RCA, gradation, and traffic volume is selected.